O'ZBEK XALQINING ETNOGENEZI VA ETNIK TARIXIGA OID ENG MUHIM MANBALAR - Bozorov Shuxrat Azamiddinovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article contains information about the ethnogenesis and ethnic history of the Uzbek people and information about the most important sources.